Environmental Awareness Moderates: The Effects of Green Service Behavior and Employee Hospitality on Green Tourist Satisfaction - Dadang Wiranta; Euis Lisnawati; Rema Mulyani (Baashima : Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2026)
This study aims to examine the influence of Green Service Behavior and Employee Hospitality on Green Tourist Satisfaction, as well as to analyze the role of Environmental Awareness as a moderating variable. With the development of the concept of sustainable tourism, human resources are required not only to provide excellent service but also to support nature conservation practices. This study focuses on the Situgunung Resort ecotourism area in Sukabumi Regency. Using a quantitative approach, data were collected through a Likert-scale survey using purposive sampling on 125 tourist respondents. Subsequently, the data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results revealed that Green Service Behavior does not have a significant influence on Green Tourist Satisfaction. Conversely, Employee Hospitality was found to have a positive and significant influence on tourist satisfaction. Furthermore, the results of the moderation test indicate that Environmental Awareness does not moderate the relationship between Green Service Behavior or Employee Hospitality and tourist satisfaction. This implies that the level of visitors’ environmental awareness whether high or low does not strengthen or weaken the impact of service on their final satisfaction. In conclusion, friendly personal interactions from employees remain the primary driver of tourist satisfaction in sustainable destinations.